Police brutality, racial profiling, and discrimination in the criminal justice system - Egharevba, Stephen (Advances in religious and cultural studies (ARCS) book series, 2017)
"This bookis an authoritative reference source for the latest scholarly material on social problems involving victimization of minorities and police accountability and presenting relevant perspectives on a global and cross-cultural scale"--